Determinants of Migration Flows in Highly Skilled Migrants Interprovince in Indonesia - I Wayan Krisnandita (Populasi, 2023)
Migration and regional inequality are two interrelated concepts. Inequality between regions can lead to migration. High-skilled migration, or migration of high-quality human resources, has great potential to reduce interregional disparities by helping development in the destination area. However, in reality, the flow of high-skilled migration tends to lead to more advanced provinces, especially the capital and its surroundings. This condition causes disparities between regions to increase. This study analyzes the phenomenon of internal high-skilled migration between provinces in Indonesia at a macro level using a modified gravity model approach and is estimated using the zero-inflated negative binomial (ZINB) model. The results of this study show that the number of high-skilled populations in the provinces of origin and destination, geographical distance, average wages for workers, and the percentage of agricultural workers in the destination province, as well as the stock of migrants, influence the flow of high skilled migration between provinces in Indonesia. Increasing workers’ wages, access to transportation and information/social networks, as well as industrialization outside Java, need to be carried out to attract high-skilled migrants or keep high-skilled workers to remain in their provinces to realize equity between regions.